A digital distraction? The role of digital tools and distributed intelligence in woodblock printmaking practice. Issue 3 (3rd July 2021) - Chittenden, Tara
ABSTRACT: Artists' adoption of CNC devices and related technologies is making possible novel printmaking processes and variations on techniques. Such changes suggest a need to broaden our understanding of what constitutes a print under contemporary technological conditions. This article looks at the human-machine relationship and the state of creative cognition in the act of woodblock printmaking. Connections between the printmaker's and programmer's notions of creating lines indicate different ways of thinking-drawing space and position the resulting 2D print not just as the transfer of ink from block to paper but also existing as lines of code and as a 3D space. By drawing parallels between the embodied yet distributed act of traditional Japanese woodblock printmaking and the experience of CNC computerized carving in the work of Mike Lyon, I explore how woodblock printmaking might facilitate a productive collaboration with digital carving technologies.